Delegating performance evaluation - Igor Letina; Shuo Liu; Nick Netzer (Theoretical Economics, 2020)
We study optimal incentive contracts with multiple agents when performance is evaluated by a reviewer. The reviewer may be biased in favor of the agents, but the degree of bias is unknown to the principal. We show that a contest, which is a contract in which the principal fixes a set of prizes to be allocated to the agents, is optimal. By using a contest, the principal can commit to sustaining incentives despite the reviewer's potential leniency bias. The optimal effort profile can be uniquely implemented by an all-pay auction with a cap. Our analysis has implications for various applications, such as the design of worker compensation or the allocation of research grants.
Keywords: D02; D82; M52; 330; Subjective performance evaluation; mechanism design without money; optimal delegation; optimality of contests